Combination of Short- and Longaxis MR Image Sequences for 3D Segmentation of the Left Ventricle - Säring, Dennis; Jatin Relan; Michael Groth; Kai Müllerleile; Heinz Handels (Studies in health technology and informatics, 2008)
Segmentation of the left ventricle (LV) is required to quantify LV remodeling after myocardial infarction. Therefore spatiotemporal Cine MR sequences including longaxis and shortaxis images are acquired. In this paper a new segmentation method for fast and robust segmentation of the left ventricle in 4D MR images is presented. The new approach considers the position of the mitral valve and the apex as well as the longaxis contours to generate a 3D LV surface model. The segmentation result can be checked and adjusted in the shortaxis images. Finally quantitative parameters were extracted. For evaluation the LV was segmented in eight datasets of the same subject by two medical experts using a contour drawing tool and the new segmentation tool. The results of both methods were compared concerning robustness and interaction time and intra- and interobserver differences. The presented segmentation method proved to be fast and robust and the intra- and interobserver differences are decreased significantly.
Keywords: Cardiac Volume; Endocardium; Heart Ventricles; Humans; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Magnetic Resonance Imaging, Cine; Mitral Valve; Observer Variation; Pericardium; Software Design; Stroke Volume; Ventricular Function, Left